Gambaran Profil Jaringan Lunak Pasien Berdasarkan Analisis Holdaway "Analisis Sefalometri Pada Pasien Usia 6-12 Tahun di RSGM-P FKG Usakti" (Laporan Penelitian) - Michelle Zabrina Lesilolo; Magdalena Juliani Hardja B (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Malocclusion is an occlusion that deviates from the normal state. Diagnosis and orthodontic treatment plan might use Holdaway soft tissue cephalometric analysis. Holdaway's analysis is more detailed and clear because it has 11 parameters in soft tissue measurements, namely facial angle, nasal crest distance, upper lip sulcus depth, H angle, Subnasal distance to H line, skeletal convexity, thickness of the base of the upper lip, upper lip strain, distance Li to H line, ILS distance to H line and chin thickness. Objective: To describe the soft tissue profile of patients based on Holdaway analysis in patients aged 6-12 years at RSGM-P FKG Usakti. Methods: Descriptive observational study with a cross-sectional design on orthodontic patients aged 6-12 years at RSGM-P FKG Usakti in 2018-2019. Results: The mean facial angle of the patient was 88.3°, nasal crest was 5.12 mm, the mean upper lip sulcus depth was 3 mm, the mean H angle was 16.68°, the mean Sn-H was 7.77 mm, the skeletal convexity was 3.75 mm. , the thickness of the upper lip base was 11.37 mm, the upper lip strain was 11.52 mm, the Li-H average was 2.56 mm, the ILS-H average was 2.59 mm and the chin thickness measurement was 11.09 mm. Conclusion: This study showed that the patient had an ideal upper lip sulcus depth, ILS-H distance, and chin thickness meanwhile the facial angle, H angle, and skeletal convexity are convex. The Sn-H distance, thickness of the upper lip base, upper lip strain, and Li-H distance are less than ideal, accompanied by a small nose crest distance